Gale encyclopedia of Science.-- 4th ed. - Lerner, K. Lee.; Lerner, Brenda Wilmoth (Farmington Hills, MI : Thomson Gale, 2008)
v. (paged continuously) : chiefly col. il.
Includes index
Keywords: Science -- Encyclopedia